2018
DOI: 10.21037/tgh.2018.06.05
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation, a novel paradigm in liver cancer

Abstract: Liver cancer is the sixth most prevailing cancer worldwide. Hepatocellular carcinoma (HCC), the most common form of primary liver cancer, has a rather heterogeneous pathogenesis making it highly refractive to current therapeutic approaches. Hence, HCC patients have a poor and gloomy prognosis making liver cancer the second leading cause of global cancer-related deaths. On this basis, a more global mechanism, such as post-translational modifications (PTMs) of proteins, may provide a valuable therapeutic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 134 publications
1
29
0
Order By: Relevance
“…This finding defines a molecular basis for the reported defects in the NEDD8 cycle in tumors as evidenced by an increase in protein NEDDylation (Abidi and Xirodimas, 2015). Importantly, our findings on the role of NEDP1 in the DNA damage induced apoptosis through regulation of the HSP70-APAF1 module, provide potential mechanistic insights for the reported resistance of advanced HCC tumors to chemotherapy (Abidi and Xirodimas, 2015;Delgado et al, 2018). As inhibitors for the NEDD8 pathway are in Phase II clinical trials (Abidi 17 and Xirodimas, 2015), NEDP1 levels may provide a marker for the tumor response to these inhibitors.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This finding defines a molecular basis for the reported defects in the NEDD8 cycle in tumors as evidenced by an increase in protein NEDDylation (Abidi and Xirodimas, 2015). Importantly, our findings on the role of NEDP1 in the DNA damage induced apoptosis through regulation of the HSP70-APAF1 module, provide potential mechanistic insights for the reported resistance of advanced HCC tumors to chemotherapy (Abidi and Xirodimas, 2015;Delgado et al, 2018). As inhibitors for the NEDD8 pathway are in Phase II clinical trials (Abidi 17 and Xirodimas, 2015), NEDP1 levels may provide a marker for the tumor response to these inhibitors.…”
Section: Discussionsupporting
confidence: 55%
“…GNMT is a tumor suppressor and deletion in mice results in the development of HCC (Martínez-Chantar et al, 2008). We chose this system as previous studies showed upregulation in protein NEDDylation in GNMT-/-derived HCC tumors (Delgado et al, 2018). We found that NEDP1 protein levels in liver tissue extracts are dramatically reduced in all tested HCC animals compared to control animals (Fig.…”
Section: Nedp1 Is Downregulated In Hepatocellular Carcinomamentioning
confidence: 88%
See 1 more Smart Citation
“…The deNEDDylating enzyme NEDP1 is now established as a critical regulator of protein NEDDylation, implicated in the control of several cellular processes. Decrease in NEDP1 levels was recently proposed as a molecular basis for the observed increase in protein NEDDylation observed in hepatocellular carcinoma 19,21 . Therefore, the development of inhibitors for NEDP1 will provide important tools for studying the functions for this enzyme.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies indicated a role for NEDP1 in tumour progression; The upregulation of NEDD8 in hepatocellular carcinoma was related to a decrease in the levels of NEDP1. Importantly, decrease in NEDP1 levels provides resistance of tumour cells to DNA damage induced apoptosis 9, 1921 .…”
Section: Introductionmentioning
confidence: 99%